Lanthanide(III) Complexes of 2-(N-Salicylideneamino)-4-Phenylthiazole - Sasidharan, G.N.; Mohanan, K.; Lakshmi Prabha, A.N. (Asian Journal of Chemistry, 2010)
Lanthanide(III) complexes of 2-(N-salicylideneamino)-4-phenylthiazole (HSAT) have been synthesized and characterized by elemental analytical, thermogravimetric, molar conductance, UV-visible, IR and NMR spectral data. The ligand coordinates to the lanthanide (III) ion in a tridentate fashion without deprotonation, giving complexes of the type [Ln(HSAT)2(NO3)3] and [Ln(HSAT)2(H2O)3Cl3]. The spectral data reveal that the ligand is bonded to the lanthanide ion through azomethine nitrogen, ring nitrogen and phenolic oxygen without deprotonation. The nitrate group acts in a bidentate fashion. The ligand and the metal complexes exhibit antibacterial and antifungal activities.